Gambaran Subtipe HIV-1 dengan Kadar CD4, Stadium Klinis, dan Infeksi Oportunistik Penderita HIV/AIDS di Kota dan Kabupaten Jayapura, Papua - Mirna Widiyanti (Majalah Kedokteran Bandung, 2016)
The number of HIV/AIDS cases recorded in March 2013 in Indonesia is 103,759 HIV cases and 43,347 AIDS cases. Papua is the province that has the third highest number HIV/AIDS cases with 10,881 HIV cases and 7,795 AIDS cases. The aim of this study was to identify the distribution of HIV-1 subtypes which are dominant in Papua and to identify opportunistic infections related to HIV/AIDS and their relationship with HIV-1 subtypes. This study is a cross-sectional study. The identification of HIV-1 was performed using nested-PCR and sequencing to look for HIV-1 subtypes. The study was conducted in Dok II, Abepura and Yowari VCT Hospital in Jayapura District during the period of November–December 2012. CD4 and opportunistic infections were retrieved from patient medical records. Data were analyzed statistically using chi-square test. The dominant HIV-1 subtypes found were subtype CRF01-AE, which was found in 51 people (54%), and subtype B, which was found in 43 people (46%). Of 94 HIV patients, 62 (66%) respondents suffered from pulmonary tubeculosis opportunistic infection and some patients suffered more than one type of opportunistic infections. There was no significant difference found between the HIV-1 subtypes, CD4 level, and clinicial stage. However, a significant correlation with opportunistic infections was found. It is concluded that the dominant HIV-1 subtype in Papua is CRF01_AE with tuberculosis as the most frequent opportunistic infection.